The Use of English Title in Gramedia Pustaka Utama Teenlit: A Production Analysis - Fauziah, Fitriatul (Faculty of Communications Science, Dr. Soetomo University, 2018)
The use of English language has a specific purpose and intent related to the purpose of the writers to produce good literature works and publishers who want to market these products. This study is to investigate the reason of the teenlit's producers using English titles rather than Indonesia. By using production analysis, this study focuses only on the producer's point of views, which are the Gramedia Pustaka Utama's editor and authors. Who has the power to decide the title and what the considerations are the focus of this study. The findings of this study show that actually, the producers not only consider the commercial or economic factors of the teenlit's title but also the aesthetic function that matches the theme of the whole story of the teenlit it self. The result of this study is expected to provide an understanding of the phenomenon of language hybridization that is contained in most Indonesian teenlit.